Deformation Characteristics of Lime Stabilized Clay Soil Using Finite Element Method - Md Yusof, Zeety; Roslan, Ain Soraya (Journal of Sustainable Underground Exploration, 2022)
Clay soil provides a poor working platform due to its plastic characteristics that could affect a structure’s safety and other common structure failure including excessive foundation settlement, the production of cracks in the superstructure and other structural element failure. Thus, there is a challenge for clay soil to be a support for a foundation. The objective of this study is to compile a set data from past research studies that include the parameters of untreated and treated clay soil properties as to be used in the PLAXIS 2D generate its deformation over no load and 100 kPa stress as well as increasing its shear strength and reduce the excessive settlement. Accordingly, the suitable lime content to improve clay strength can be determined. The numerical analysis is done by running the parameters collected from previous studies in PLAXIS 2D in order to generate the final deform soil. The soil with lime content 0%, 3%, 6%, and 9% deformed under both without and with loading of 100 kPa. The result that can be observed from the deformed soil, the treated clay behaved well under loading compared to the untreated. From the result, the amount of lime content did affect the properties of the soil by showing the settlement of each soil and the deformation pattern.